Possible selves in patients with right- versus left-onset Parkinson's disease. Issue 2 (4th March 2017) - Harris, Erica; McNamara, Patrick; Durso, Raymon
ABSTRACT: Possible selves can be used to self-regulate and guide behavior towards what is desired to be achieved or avoided in life. Previous work suggests laterality effects exist within the brain regarding approach and avoidance systems to achieve self-regulation. A modified version of the possible selves task was administered to 45 patients with PD (22 right-onset and 23 left-onset) and 25 community dwelling control subjects (CS). Only 11.1% of patients exhibited balance among their hoped-for and feared possible selves versus 28% of CS. More right-onset patients used a promotion strategy whereas more left-onset patients used a prevention strategy. Patients with left-onset PD thought more about their feared selves, exhibiting reduced goal-directed behavior. Findings among the left-onset group indicate relative dependence of self-regulation on right-sided avoidance brain systems. This may point to an inability to move away from negative outcomes and to work towards rewarding outcomes, which could affect psychological health.